Education for the Sustainability transition - John, Michele (Taylor and Francis, 2025)
Whilst many education institutions are cognisant of the increasing pressure from global sustainability challenges, few are focused on the structural, curricula or pedagogical changes needed within their education systems that will help to meet the challenges associated with the major sustainability transitions of the 21st century. The development of a ‘sustainability mindset’ that includes key sustainability concepts, thinking and values and global citizenship, is an important responsibility in modern education. New definitions of sustainability are emerging that are increasing and re-imagining the responsibilities involved in the sustainability transition. Regenerative sustainability paradigms will focus on net positive outcomes from the interdependent interactions that occur within the three pillars of sustainability—economic, social, and environmental systems—where the whole Earth’s well-being is considered in our sustainability decision making.